An Informational Object Model for ODP Applications - El Ouahidi, Bouabid; Bouhdadi, Mohamed (Malaysian Journal of Computer Science, 2000)
The Reference Model-Open Distributed Processing (RM-ODP) provides a framework for the standardization of Open Distributed Processing (ODP). It defines an object model and an architecture for the construction of ODP systems in terms of five viewpoints. However, the RM-ODP is abstract and therefore cannot be easily applicable. Indeed, several issues must be addressed. The objective of this paper is twofold. Firstly, based on RM-ODP itself, we define a concrete typing system for the ODP information objects. This model is a contribution for defining the ODP type repository function. Secondly, we show that the Object Constraint Language (OCL) can be used for the ODP type descriptions, and for the ODP information viewpoint specifications. Using OCL we apply that typing system to describe the ODP trading information viewpoint.